2014
DOI: 10.1159/000364953
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Resting Energy Expenditure Calculations in Unselected Overweight and Obese Patients

Abstract: Aims: Measurements of resting energy expenditure (REE) were compared with the data of 14 equations to determine their accuracy. Methods: REE measurements by indirect calorimetry in 1,032 unselected overweight and obese men (n = 306) and women (n = 726) were compared with calculations by 14 different formulas. Results: The mean (± SD) values calculated with the Owen, Robertson and Reid and WHO-I equations were not significantly different from our measurement of 1,682 ± 441.9 kcal/24 h. The values obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…The low individual accuracy and agreement of pREE observed in the present study have also been observed among the general obese population (6)(7)(8) . Frankenfield et al (6) showed that the prediction rate was lower and individual variation errors were higher in pREE of overweight and obese adults than in individuals with normal weight.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The low individual accuracy and agreement of pREE observed in the present study have also been observed among the general obese population (6)(7)(8) . Frankenfield et al (6) showed that the prediction rate was lower and individual variation errors were higher in pREE of overweight and obese adults than in individuals with normal weight.…”
Section: Discussionsupporting
confidence: 55%
“…The low individual accuracy and agreement of pREE observed in the present study have also been observed among the general obese population . Frankenfield et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors stated that the differences between the predicted and the measured RMR depended on the absolute values of the RMR measured and that predictive equations are specific for the population from which they were derived. This hypothesis is reinforced by Schusdziarra et al [37], who argued that different equations provide accurate estimates in older and obese individuals. These authors added that although the equations are valid for group analysis, prediction is generally invalid for individual evaluations.…”
Section: Discussionmentioning
confidence: 93%